2020
DOI: 10.1021/jacs.9b13701
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Modulation of Hybrid Perovskite Solar Cells via Bifunctional Halogen Bonding Revealed by Two-Dimensional 19F Solid-State NMR Spectroscopy

Abstract: There has been an ongoing effort to overcome the limitations associated with the stability of hybrid organic-inorganic perovskite solar cells by using different organic agents as additives to the perovskite formulations. The functionality of organic additives has been predominantly limited to exploiting hydrogen bonding interactions, with the relevant atomic-level binding modes remaining elusive. Herein, we introduce a new bifunctional supramolecular modulator, 1,2,4,5-tetrafluoro-3,6-diiodobenzene, which inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 50 publications
(111 reference statements)
3
116
0
Order By: Relevance
“…In the case of interfacial engineering, using molecular assemblies (Bai et al, 2019;Milić et al, 2019b;Zhang et al, 2019) and graphene composites (Arora et al, 2017;Milić et al, 2018) at the interface of charge selective transport layers was found to be particularly effective in stabilizing the perovskite devices (Ehrler and Hutter, 2020). This is often related to blocking the ions from the neighboring layers (Domanski et al, 2016), although very few systematic investigations demonstrate this particular mode of action (Merdasa et al, 2020;Ruiz-Preciado et al, 2020). Moreover, using appropriate selective charge-selective extraction layers can suppress the (photo)redox degradation pathways (Wei et al, 2020).…”
Section: Mitigationmentioning
confidence: 99%
“…In the case of interfacial engineering, using molecular assemblies (Bai et al, 2019;Milić et al, 2019b;Zhang et al, 2019) and graphene composites (Arora et al, 2017;Milić et al, 2018) at the interface of charge selective transport layers was found to be particularly effective in stabilizing the perovskite devices (Ehrler and Hutter, 2020). This is often related to blocking the ions from the neighboring layers (Domanski et al, 2016), although very few systematic investigations demonstrate this particular mode of action (Merdasa et al, 2020;Ruiz-Preciado et al, 2020). Moreover, using appropriate selective charge-selective extraction layers can suppress the (photo)redox degradation pathways (Wei et al, 2020).…”
Section: Mitigationmentioning
confidence: 99%
“…In spite of the number of important studies devoted to halide perovskites, however, the number of DFT simulations targeting NMR parameters is much more scarce. Just in the last years, few NMR investigations included estimates of the magnetic shielding tensor via DFT simulations, mainly exploiting the molecular approach from quantum‐chemistry [31,34,51–54] . Here, reliable models for the halide perovskite material are obtained by cutting out a finite cluster [55] .…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the ambiguity of the PDF data, solid-state 19 (Table T3, Supporting Information), which is consistent with fluoride in a diamagnetic perovskite environment. 40,41 Interestingly, all of the other signals correspond to much shorter 19 F T 1 values of 0.3-0.4 s (Table T3), consistent with fluoride environments that are influenced by conducting or donor electrons. [40][41][42] DFT calculations of several structural models selected from the phase diagram for fluoride intercalation into ReO 3 predict an isotropic 19 F chemical shift of -141 ppm for mono-ReO 3 F, close to the values of several of the measured signals.…”
mentioning
confidence: 55%
“…40,41 Interestingly, all of the other signals correspond to much shorter 19 F T 1 values of 0.3-0.4 s (Table T3), consistent with fluoride environments that are influenced by conducting or donor electrons. [40][41][42] DFT calculations of several structural models selected from the phase diagram for fluoride intercalation into ReO 3 predict an isotropic 19 F chemical shift of -141 ppm for mono-ReO 3 F, close to the values of several of the measured signals. By comparison, the DFT calculations predict the isotropic chemical shift of a model structure with 7-coordinate distorted-octahedra to be near -73 ppm and of tet-FReO 3 to be near -11 ppm, neither of which are experimentally observed ( Figure S10).…”
mentioning
confidence: 55%